Constitutive expression of IL-18 and IL-18R in differentiated IEC-6 cells: effect of TNF-alpha and IFN-gamma treatment - Kolinska, Jirina; Lisa, Vera; Clark, Jessica A; Kozakova, Hana; Zakostelecka, Marie; Khailova, Ludmila; Sinkora, Marek; Kitanovicova, Andrea; Dvorak, Bohuslav (Journal of interferon & cytokine research, 2008)
The multifunctional cytokine interleukin-18 (IL-18) is an important mediator in intestinal inflammatory processes. The aim of this study was to evaluate the constitutive expression of IL-18 and its receptors (IL-18Ralpha and IL-18Rbeta) in intestinal epithelial cells (IEC) stimulated by tumor necrosis factor-alpha (TNF-alpha) and interferon-gamma (IFN-gamma). In addition, cellular proliferation and evaluation of brush border enzymes as differentiation markers were studied. Nontransformed rat intestinal epithelial IEC-6 cells were grown on an extracellular matrix (ECM) in medium with or without TNF-alpha, IFN-gamma, or a combination of both. Gene expression of IL-18, its receptors and apoptotic markers was evaluated using real-time PCR. Expression of IL-18Ralpha protein was demonstrated by flow cytometry and Western blot. Enzymatic activities of brush border enzymes and caspase-1 were determined. The constitutive expression of IL-18, IL-18Ralpha and IL-18Rbeta mRNAs and proteins were detected in IEC-6 cells. The biologically active form of IL-18 was released in response to TNF-alpha and IFN-gamma treatment. Exogenous IL-18 had no effect on cellular proliferation, brush border enzyme activities, and gene expression of apoptotic markers. However, the addition of IL-18 stimulated production and release of the chemokine IL-8. These data suggest that IEC-6 cells may be not only a source of IL-18 but also a target for its action.
Keywords: Gene Expression Regulation; RNA, Messenger; střeva; Cell Line; Culture Media; Cell Count; biologické markery; Interferon-gamma; epitelové buňky; Tumor Necrosis Factor-alpha; Biomarkers; kultivační média; Chemokine CCL2; Epithelial Cells; buněčná diferenciace; chemokin CCL2; interferon gama; Interleukin-18 Receptor beta Subunit; kaspasa 1; počet buněk; polymerázová řetězová reakce s reverzní transkripcí; Interleukin-18 Receptor alpha Subunit; Interleukin-18; krysa rodu Rattus; Caspase 1; Cell Membrane; interleukin-18; Animals; receptor interleukinu-18 - alfa-podjednotka; receptor interleukinu-18 - beta-podjednotka; zvířata; regulace genové exprese; buněčná membrána; Rats; Reverse Transcriptase Polymerase Chain Reaction; apoptóza; buněčné linie; TNF-alfa; Intestines; messenger RNA; Apoptosis; Cell Differentiation